Mismatch between the quality of dwelling units and residents’ health condition in elderly housing with supportive services - Motohiro Sannomiya; Byung Joon Hwang; Yoshihiro Suzuki (Japan Architectural Review, 2019)
Abstract This work aims to clarify mismatches between the health condition of residents of the Elderly Housing with Supportive Services (EHSS) and quality of dwelling unit to understand how to improve the quality of the living environment. This work reviews development trends in EHSS and population growth to understand the difficulties faced in improving EHSS in the community. Data were collected from the information disclosure system on the WEB site and through a questionnaire survey of EHSS management bodies. Although residents in regions with large populations have more variety, the plan‐service types available in smaller regions had disproportionately high amounts of room types with moderate to high care, despite that distribution of residents’ necessary care levels were constant across region size. Development of EHSS for self‐supporting residents or those needing mild care is a necessity. Mismatches also emerged between health condition, household size, and degree of care. Many couples were living in R‐housing, displaying a difficulty in EHSS to meet the needs of couples who wish to continue living together. Many residents able to live independently are living in R‐housing, restricting their daily living activities, and presenting a risk of losing the motivation to live.